2019
DOI: 10.1155/2019/1648576
|View full text |Cite
|
Sign up to set email alerts
|

New Stability Criteria for Event‐Triggered Nonlinear Networked Control System with Time Delay

Abstract: This note focuses on the stability and stabilization problem of nonlinear networked control system with time delay. To alleviate the burden of transformation channel and shorten the dynamic process simultaneously, an improved event-triggered scheme is proposed. This paper employs an improved time delay method to enhance the performance and reduce the delay upper bound conservatism. Less conservative stability criteria related to the order N are derived by establishing an augmented Lyapunov-Krasovskii functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…In [25], less conservative stability conditions for delayed neural networks have been derived through the use of the free-matrix-based inequality. By employing the Bessel-Legendre-based inequality and reciprocally convex inequality, the stability and stabilization have been derived in [26] for event-triggered nonlinear networked control system with time delay. It is found that the canonical N -order Bessel-Legendre inequality method presented in [32] and generalized N -order free-matrix-based inequality method proposed in [35] can provide a lower bound for L (t) as tight as possible if N goes to infinity, which can greatly decrease the conservatism of the derived stability criterion based on the proper Lyapunov functional.…”
Section: Many Significant and Valuable Results Have Been Obtainedmentioning
confidence: 99%
See 1 more Smart Citation
“…In [25], less conservative stability conditions for delayed neural networks have been derived through the use of the free-matrix-based inequality. By employing the Bessel-Legendre-based inequality and reciprocally convex inequality, the stability and stabilization have been derived in [26] for event-triggered nonlinear networked control system with time delay. It is found that the canonical N -order Bessel-Legendre inequality method presented in [32] and generalized N -order free-matrix-based inequality method proposed in [35] can provide a lower bound for L (t) as tight as possible if N goes to infinity, which can greatly decrease the conservatism of the derived stability criterion based on the proper Lyapunov functional.…”
Section: Many Significant and Valuable Results Have Been Obtainedmentioning
confidence: 99%
“…In addition, the proposed looped Lyapunov functional in this paper can be also extended to study the control synthesis problem for other various dynamical system such as networked control system [26], neural networks [43], [44], T-S fuzzy systems [45], and so on. By employing the Lyapunov functional obtained from the method, future work will focus on the research of stability, stabilization and synchronization control for the above mentioned systems.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics include invariant, random, correlation, or independent. 13 However, the controlled object in NCS actually includes both the physical object and the control network. Even if the model of the physical object is accurate, because of the complexity of the control network, it is impossible to use mathematical tools such as differential equation or difference equation to describe it, so NCS is still unknown in essence.…”
Section: Introductionmentioning
confidence: 99%